Antiproliferative, Antiangiogenic, and Antimetastatic Therapy Response by Mangiferin in a Syngeneic Immunocompetent Colorectal Cancer Mouse Model Involves Changes in Mitochondrial Energy Metabolism - Rodriguez-Gonzalez, Julio César; Hernández-Balmaseda, Ivones; Declerck, Ken; Pérez-Novo, Claudina; Logie, Emilie; Theys, Claudia; Jakubek, Patrycja; Quiñones-Maza, Olga Luisa; Dantas-Cassali, Geovanni; Carlos dos Reis, Diego; Van Camp, Guy; Lopes Paz, Miriam Teresa; et al. (Frontiers in Pharmacology, 2021)
In spite of the current advances and achievements in cancer treatments, colorectal cancer (CRC) persists as one of the most prevalent and deadly tumor types in both men and women worldwide. Drug resistance, adverse side effects and high rate of angiogenesis, metastasis and tumor relapse remain one of the greatest challenges in long-term management of CRC and urges need for new leads of anti-cancer drugs. We demonstrate that CRC treatment with the phytopharmaceutical mangiferin (MGF), a glucosylxanthone present in Mango tree stem bark and leaves (Mangifera Indica L.), induces dose-dependent tumor regression and decreases lung metastasis in a syngeneic immunocompetent allograft mouse model of murine CT26 colon carcinoma , which increases overall survival of mice. Anti-metastatic and anti-angiogenic MGF effects could be further validated in a wound healing in vitro model in human HT29 cells and in a matrigel plug implant mouse model. Interestingly, transcriptome pathway enrichment analysis demonstrates that MGF inhibits tumor growth, metastasis and angiogenesis by multi-targeting of mitochondrial oxidoreductase and fatty acid -oxidation metabolism, PPAR, SIRT, NFκB, Stat3, HIF, Wnt and GP6 signaling pathways. MGF effects on fatty acid -oxidation metabolism and carnitine palmitoyltransferase 1 (CPT1) protein expression could be further confirmed in vitro in human HT29 colon cells. In conclusion, antitumor, antiangiogenic and antimetastatic effects of MGF treatment hold promise to reduce adverse toxicity and to mitigate therapeutic outcome of colorectal cancer treatment by targeting mitochondrial energy metabolism in the tumor microenvironment.